2020
DOI: 10.1093/ofid/ofaa124
|View full text |Cite
|
Sign up to set email alerts
|

In Full Flow: Left Ventricular Assist Device Infections in the Modern Era

Abstract: With the rising prevalence of heart disease in the United States, there is increasing reliance on durable mechanical circulatory support (MCS) to treat patients with end-stage heart failure. Left ventricular assist devices (LVADs), the most common form of durable MCS, are implanted mechanical pumps that connect to an external power source through a transcutaneous driveline. First-generation LVADs were bulky, pulsatile pumps that were frequently complicated by infection. Second-generation LVADs have an improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 75 publications
3
79
0
Order By: Relevance
“…The literature mentions up to 51.9% infections after implantation of continuous-flow LVADs [24]. A recent review mentions 19-39% infection rates after implantation of second-and third-generation LVADs [25]. A Swiss group recently reported 45% LVAD-related infection after HeartMate 3 implantation, including driveline ex-site infections [26].…”
Section: Major Adverse Eventsmentioning
confidence: 99%
“…The literature mentions up to 51.9% infections after implantation of continuous-flow LVADs [24]. A recent review mentions 19-39% infection rates after implantation of second-and third-generation LVADs [25]. A Swiss group recently reported 45% LVAD-related infection after HeartMate 3 implantation, including driveline ex-site infections [26].…”
Section: Major Adverse Eventsmentioning
confidence: 99%
“…In additionally, previous studies about old generation pumps reported that the pump pocket site is a poorly vascularized space. 21 Hematoma or seroma formation in the large subcutaneous space created in this procedure may also lead to compromised wound healing and subsequent infection. 20 All these factors delay wound healing and cause infection in the driveline tunnel between thoracotomy incision and driveline exit site.…”
Section: Discussionmentioning
confidence: 99%
“…13 Practice patterns are variable with many institutions continuing to use suppression routinely for superficial DLI. 14,15 In our institution, there was a change in the practice pattern in the latter part of the study period (2013)(2014)(2015), during which 81% of patients were placed on CSA compared with only 48% in the earlier study period. with resolution of all symptoms and signs of infection.…”
Section: F I G U R E 1 Kaplan-meier Curve For Infection Recurrence Among Those Who Received Suppression and Those Who Did Notmentioning
confidence: 96%
“…13 However, many centers still opt to place patients on chronic suppressive antibiotics (CSA) therapy following clinical response with the goal to prevent relapse with the same organism. 14,15 Few studies tried to answer this question, but they were limited by small numbers. 10 We sought to examine risk factors for relapse of DLI, and whether CSA is associated with reduced risk of relapse and progression to deeper infection in this population.…”
Section: Introductionmentioning
confidence: 99%